Institutions and abused women: an interactional model to access justice in India. Issue 4 (19th May 2018) - Singh, Sudhir Pratap; Mahapatro, Meerambika
ABSTRACT: The discourse on domestic violence has steadily moved from solely the realm of private family affairs into the institutional domain, through changing perceptions and the enactment and enforcement of laws. This article aims to understand how women approach institutions and how institutions perceive, translate, and respond to complaints within human rights discourses. The study analysed all cases registered in a family counselling centre in Rajasthan, India, with ten cases then randomly selected for in-depth interviews. The institutions are a catalyst of social change; however, they need to partner with specialists for medical interventions, and network with line departments more effectively to improve social resilience.